3‐O‐Glyceryl‐2‐O‐hexyl ascorbate suppresses melanogenesis by interfering with intracellular melanosome transport and suppressing tyrosinase protein synthesis. (7th November 2017) - Taira, Norihisa; Katsuyama, Yushi; Yoshioka, Masato; Okano, Yuri; Masaki, Hitoshi
Summary: Background: Ascorbic acid (AsA) has multifunctional benefits on skin beauty, such as the reduction in oxidative stress and the induction of collagen production. Among them, the prevention and improvement of skin pigmentation by AsA is a most important benefit for people. However, it is well known that AsA not only is quite unstable in formulations but it also has a low capability of skin penetration due to its hydrophilic property. In addition, existing water‐soluble AsA derivatives that were developed to improve its stability also have low skin penetration. Aim: To investigate the potential of a newly synthesized amphiphilic derivative of AsA, 3‐ O ‐Glyceryl‐2‐ O ‐hexyl ascorbate (VC‐HG), which has an added glyceryl group and a hexyl group, on skin beauty focusing on its skin lightening/whitening effects. Methods: DNA microarray analysis and real‐time PCR were used to clarify the effects of VC‐HG on melanogenesis using B16 mouse melanoma cells. The effects of VC‐HG on melanin synthesis, tyrosinase protein levels, and the inhibition of tyrosinase activity were evaluated. Results: DNA microarray analysis revealed that treatment with VC‐HG downregulated the expression of genes encoding tyrosinase and MyosinVa. Further, real‐time PCR analysis showed the downregulation of tyrosinase, MyosinVa, Rab27a, and Kinesin mRNAs following VC‐HG treatment. In addition, VC‐HG caused decreases in tyrosinase protein levels and melanin synthesis. Conclusion: We conclude that VC‐HG has an impact on skin lightening/whitening by inhibiting tyrosinase protein synthesis and interfering with intracellular melanosome transport.